Evaluation of carcass quality of live pigs at weights of 60 kg and 90 kg - Uusisalmi, Unto (Agricultural and Food Science, 1971)
The possibility of predicting the carcass quality from live pigs at weights of c. 60 kg and c. 90 kg was investigated on progeny testing pigs (n = 236) of Landrace and Yorkshire breeds. In both weight classes the thickness of the fat was measured with an ultrasonic instrument on the back, hams and shoulders, as well as the depth of the m. long, dorsi. Exterior measurements and points evalutations were also made. The pigs were slaughtered at a weight of 90 kg, after which a conventional carcass evaluation was made. The least squares method (HARVEY 1966) was used to analyse the results in order to establish the effect of the live weight, the group, breed and sex. After calculating an initial correlation matric (179 x 179), 20 characteristics obtained from the carcass evaluation were taken as functions, and 30 characteristics of both the live weights taken as optional explanatory variables, for further processing by stepwise multiple regression analysis. The back fat can be estimated from measurements at live weights of 60 kg (R2 = 0.53) and 90 kg (R2 = 0.75). The fat estimations obtained from the two weight classes showed similarities. The average back fat measured at a live weight of 90 kg correlated significantly with the average back fat measured from the carcass (r = 0.82***, r2 = 0.67), and the side fat at a live weight of 90 kg with the s.o.l. from the carcass (r = 0.79***, r2 = 0.62). Prediction of the area of the m. long. dorsi was poor in both the weights (R2 = 0.27—0.29).